[Laiškai] / Šaniavskis (Szaniawski) Kasparas - Adomui Zavadskiui. - (:unkn) unknown (My University, 1855)
4 laiškai apie knygų atsiuntimą (yra sąrašai), "Tygodnik lekarski" prenumeratą.
Keywords: Rankraščiai